USAHA PERIKANAN TERPADU DI FAKULTAS PERIKANAN UNIVERSITAS PGRI PALEMBANG - Haris, Helmi; Widayatsih, Tri; Asmawati, Asmawati (Ngayah: Majalah Aplikasi IPTEKS, 2019)
The Faculty of Fisheries, University of PGRI Palembang has two campuses, namely at Campus A Plaju for administrative and lecture activities, while for practical activities, field practice, research and training, specifically for the Faculty of Fisheries located at Campus C Sematang Borang-Palembang. Campus C Sematang This place occupies about 1 ha of land, which has been equipped with Office Room facilities, Multipurpose Room for meetings, Lecture Rooms, Fish Hatchery Workshop, Fisheries Product Processing Workshop, Entrepreneurship Workshop, Fish Feed Production Room, Cement Pond for seeding, Bioflog for enlargement and floating net cages for enlargement. Campus C is specifically intended for the Fisheries Faculty which was completed in 2012. In 2013 and 2014 the Chair of the Proposal Team received Community Service Grant as Team Leader for the Campus Innovation Product Business Development Program Scheme (PPUPIK) entitled "Establishment of Scale Fish Feed Factory Home Industry as a Source of Income Generating for the Faculty of Fisheries, University of PGRI Palembang ".For the Lab scale, this activity has been going well and has good prospects, the problem faced is that fisheries business activities on campus C of the Faculty of Fisheries have been running, but the activities are still partial, each field moves individually (not yet integrated management). The solution offered is that with this PPUPIK "Integrated Fisheries Business" activity all business fields are managed in an integrated manner, so that each business sector can support and strengthen each other. For this reason, on this occasion we from the Faculty of Fisheries began to develop activities in an integrated manner, starting from ornamental fish hatchery and consumption, enlarging consumption fish, making feed, processing fishery products, marketing results and training and training in fisheries for users and communities who need.The results of the implementation of the activity indicate that the activities of the Business Unit Establishment in PT Science and Technology based have been established with the name "Faculty of Fisheries Entrepreneurship Unit" with Decree of the Dean of the Faculty of Fisheries No. 294 / A.16 / F.Perik / UNIV.PGRI / 2017 dated July 3, 2017 concerning the Establishment of the Entrepreneurship Unit at the Faculty of Fisheries, University of PGRI Palembang. The products that have been produced to date are: a) Catfish Seeds, Koi and Gurami, b) Consumption Fish (Catfish and Tilapia), c) Ornamental Fish (Koi Fish), d) Processed Products (Pundang Seluang and Various form of Cork Fish Kemplang Crackers). From the results of business analysis, this activity is feasible to do with B / C ratio = 1.466, Break Even Point (BEP) = Integrated Fisheries Business Input point reached when production reaches 4,611.36 Catfish seeds + 3,458.52 Gurami seeds + 2,305.68 Koi seed + 345.85 kg consumption Catfish + 576.42 kg consumption Gouramy fish + 5,764.20 Koi ornamental fish + 23.0 fishery products processed package, Return of Investment (ROI) 18.48% and Pay Back Period (PBP) ) = 20,645 Months.Outputs generated from this activity are 1) Establishment of Business Units in Science and Technology-based PT, 2) Products, 3) National Journal of Accredited Community Service, 4) Presentation of papers, 5) Draft of Teaching Materials, and 6) Draft Patents / Intellectual Property Rights.